Synthesis and Characterization of Endcapped Hyperbranched Polyesters - Karpagam, S.; Guhanathan, S. (Asian Journal of Chemistry, 2010)
The synthesis of third generation of hyperbranched polyester (HBPE) based on AB2 type monomer, 2,2-bis(hydroxymethyl) propionic acid (bis-MPA) and phloroglucinol as a core molecule via melt condensation procedure with p-TSA as a catalyst. Efforts have been taken for the endcapping of hyperbranched polyester by using phosphorus containing indole and imidazole (IN-PD and IM-PD) to form N-heterocyclic based polyesters (IN-HBPE and IM-HBPE). The synthesized compounds were subjected to characterization viz., FT-IR, 1H and 13C NMR and elemental analysis. The spectral studies were supports the formation of compounds. 13C NMR gives the information about degree of branching of these polymers.